Unveiling the twinning and dynamic recrystallization behavior and the resultant texture evolution in the extruded Mg-Bi binary alloys during hot compression. (10th April 2022) - Zhang, Yu-qin; Cheng, Wei-li; Yu, Hui; Wang, Hong-xia; Niu, Xiao-feng; Wang, Li-fei; Li, Hang
Abstract: The twinning behavior, dynamic recrystallization (DRX) mechanism and the resultant texture evolution of the extruded Mg- x Bi ( x =0.5 wt.%, 2.0 wt.%) alloys were systematically investigated during hot compression at the strain rate of 10 s −1 and temperature of 200°C. The results indicate that the types and intensities of the texture are greatly dependent on the twining behavior and DRX mechanism. At the initial stage, the evolution of texture is mainly domination by the formation and variation of { 10 1 ¯ 2 } extension twins, which is beneficial to the compression direction (CD) -tilted basal texture. With an increase in the strain, the texture evolution is more greatly regulated by the DRX mechanism. Besides, the pyramidal < c  +  a > slip and basal < a > slip are activated during the compression process, resulting in the Schmid factors (SF) of pyramidal slip remain at ∼0.4 and the average SFs for basal < a > slip increase from 0.2 to 0.34 as the strain increase. These findings provide a new insight into controlling the texture of wrought Mg-Bi-based alloys during hot deformation processing. Highlight: The deformation mechanisms of extruded Mg-Bi alloys during compression are revealed. The CD-tilted basal texture is greatly related to the occurence of extension twins. Twinning and DRX behavior are inhibited by the nano-scaled precipitated Mg3 Bi2 phase. The pyramidal slip can be activated during compression. Abstract : Image, graphical abstract .